Sympathetic nerve traffic and baroreflex function in optimal, normal, and high-normal blood pressure states. Issue 7 (July 2015) - Seravalle, Gino; Lonati, Laura; Buzzi, Silvia; Cairo, Matteo; Quarti Trevano, Fosca; Dell'Oro, Raffaella; Facchetti, Rita; Mancia, Giuseppe; Grassi, Guido
Abstract : Objective: Adrenergic activation and baroreflex dysfunction are common in established essential hypertension, elderly hypertension, masked and white-coat hypertension, resistant hypertension, and obesity-related hypertension. Whether this autonomic behavior is peculiar to established hypertension or is also detectable in the earlier clinical phases of the disease, that is, the high-normal blood pressure (BP) state, is still largely undefined, however. Methods: In 24 individuals with optimal BP (age: 37.1 ± 2.1 years, mean ± SEM) and in 27 with normal BP and 38 with high-normal BP, age matched with optimal BP, we measured clinic, 24-h and beat-to-beat BP, heart rate (HR), and muscle sympathetic nerve activity (MSNA) at rest and during baroreceptor stimulation and deactivation. Measurements also included anthropometric as well as echocardiographic and homeostasis model assessment (HOMA) index. Results: For similar anthropometric values, clinic, 24-h ambulatory, and beat-to-beat BPs were significantly greater in normal BP than in optimal BP. This was the case when the high-normal BP group was compared to the normal and optimal BP groups. MSNA (but not HR) was also significantly greater in high-normal BP than in normal BP and optimal BP (51.3 ± 2.0 vs. 40.3 ± 2.3 and 41.1 ± 2.6 bursts per 100 heartbeats, respectively, P  < 0.01). The sympathetic activation seen in high-normal BP was coupled with an impairment of baroreflex HR control (but not MSNA) and with a significant increase in HOMA Index, which showed a significant direct relationship with MSNA. Conclusion: Thus, independently of which BP the diagnosis is based, high-normal BP is a condition characterized by a sympathetic activation. This neurogenic alteration, which is likely to be triggered by metabolic rather than reflex alterations, might be involved, together with other factors, in the progression of the condition to established hypertension.